Meredam Stigma dengan Komunikasi dan Sastra (Komunikasi Stigma dalam Cerpen Jenggo Karya Putu Wijaya) - Andika Hendra Mustaqim (Wanastra: Jurnal Bahasa dan Sastra, 2020)
Abstract - The purpose of this study is to explore how to explore communication and literary perspectives on the study of Jenggo short story by Putu Wijaya's stigma communication. The focus of the stigma communication studied is how the community's stigma about a transvestite is considered weak. Pansy stigma arises in communication that focuses on messages. This research method is content analysis with a qualitative approach with a critical constructivist paradigm. This study analyzes stigma communication with the theory put forward by Smith (2007) with the perspective of sociology and communication by Durkheim (1947) and Goffman (1963). The results of this study lead to stigma communication that occurs in Jenggo short story including signs, labeling groups, responsibilities, hazards, to the impact of messages and the process of sharing messages. This research also proves the meaning of messages in stigma communication. In an effort to ward off stigma, literature has a big role because it is able to provide other perspectives that encourage stigma communication that is more transparent and responsible for the harmony and lasting climate of peace in society. Building positive communication within the community is expected to have an impact on the construction of stigma communication that leads to a healthy and plural society.Keywords: Stigma, Communication, Stigma Communication, Jenggo, Putu WijayaAbstrak  - Tujuan penelitian ini adalah untuk mengeksplorasi bagaimana menangkal stigma dengan perspektif komunikasi dan sastra pada kajian komunikasi stigma cerpen Jenggo karya Putu Wijaya. Fokus stigma yang dikaji adalah bagaimana stigma masyarakat tentang orang banci yang dinilai lemah. Stigma banci muncul dalam komunikasi yang berfokus pada pesan. Metode penelitian ini adalah analisis isi dengan pendekatan kualitatif dengan paradigma konstruktivis kritis. Penelitian ini menganalisis komunikasi stigma dengan teori yang dikemukakan Smith (2007) dengan perspektif sosiologi dan komunikasi Durkheim (1947) dan Goffman (1963). Hasil penelitian ini mengarah kalau komunikasi stigma yang terjadi pada cerpen Jenggo meliputi tanda, pelabelan kelompok, tanggung jawab, bahaya, hingga dampak pesan dan proses berbagi pesan. Penelitian ini juga membuktikan tentang arti pesan dalam komunikasi stigma. Dalam upaya menangkal stigma, sastra memiliki peran besar karena mampu memberikan perspektif lain yang mendorong komunikasi stigma lebih transparan dan bertanggung jawab demi keharmonisan dan kelanggengan iklim perdamaian di masyarakat. Membangun komunikasi yang positif di dalam komunitas diharapkan bisa memberikan dampak konstruksi komunikasi stigma yang mengarahkan ke masyarakat yang sehat dan plural.Kata kunci: Stigma, Komunikasi, Komunikasi Stigma, Jenggo, Putu Wijaya